Toward estimating noise–power–distance curves for propeller-powered zero-emission hydrogen aircraft - Amargianitakis, Daniel C.; Self, Rodney; Torija, Antonio J.; Proenca, Anderson R.; Synodinos, Athanasios P. (American Institute of Aeronautics and Astronautics (AIAA), 2024)
As part of the UK Research and Innovation project New Aviation, Propulsion, Knowledge and Innovation Network (NAPKIN), a high-level framework was developed for the assessment of the noise impact of the proposed regional-sized hydrogen-powered aircraft. This study consists of the methodology used to generate the industry-standard noise–power–distance (NPD) curves from individual component noise analysis, specifically propeller tonal noise. The model is based on an asymptotic analysis of a frequency domain propeller tonal noise model combined with a linear approximation, taking advantage of the logarithmic nature of noise. An error analysis on the linear approximation assumption proves that the relative error between predicted and actual values of the noise remains below 10% for appropriately chosen baseline points. Verification of the framework was achieved through a bench-marking procedure that compared predictions of departure NPD curves for current technology regional aircraft against published ones over a range of operational power settings. Finally, departure and approach NPD predictions for three of the NAPKIN hydrogen concept aircraft are presented. Concepts featuring a larger, slower-rotating propeller with an increased number of blades relative to the reference aircraft showed benefits over the reference aircraft, despite, in some cases, increases in maximum takeoff weight.